Olgular Eşliğinde Anestezi Yönetimi III - Temel, Hakan; Gündüz, Emel; Akpınar, Hatice; Bıçakcıoğlu, Murat; Altınışık, Uğur; Altınışık, Hatice Betül; Sayan, Mihrican; Kacıroğlu, Ahmet; Çetin, Mustafa Levent; Oluş, Fatih; Babun, Hüseyin; Ersoy, Zeynep; et al. (Academician Publishing Book DOI Portal, 2023)
-